Why do Bangladeshi farmers adopt Zero Tillage? (ex-post, outcome level) - CGIAR Research Program on Maize (2021)
findings with relevance for S / SE Asia. Based on farm household survey, MAIZE scientists determined the factors influencing CA-T adoption and its intensity: Age, cropping system, climate, soil, machinery.